CTLA-4 Haploinsufficiency Presenting as Extensive Enteropathy in a Patient With Very Early Onset Inflammatory Bowel Disease. Issue 3 (12th August 2021) - Tran, Ngoc N.; Setty, Mala; Cham, Elaine; Chan, Alice Y.; Ali, Sabina
Abstract : Patients with very early onset inflammatory bowel disease (VEO-IBD) have a higher incidence of monogenic disease compared to older age groups. Age, alone, is a strong predictor for monogenic disease. We discuss a case of VEO-IBD in which the patient presented with severe and refractory enteropathy, leading to diagnosis of CTLA-4 haploinsufficiency. Genetic workup showed de novo heterozygous deletions of the CTLA-4 and ICOS genes. This case was unique, as the patient did not have the other manifestations commonly present with the disease. We advocate for early and routine genetic workup of VEO-IBD, as patients with monogenic IBD have high morbidity and mortality, if inadequately treated. Our patient did not respond to conventional treatment modalities and required targeted treatment with Abatacept, a CTLA-4 agonist.